In the name of God: Managing risk in Islamic finance - Valentino Cattelan (The European Association for Banking and Financial History (EABH), 2014)
In Against the gods: the remarkable story of risk (1996), Peter L. Bernstein illustrates how the mastery of risk has driven modern Western society into converting 'the future from an enemy into an opportunity'. Far from being an antagonist, as the unpredictable whim of gods or mysterious fate, this story has transformed the future into a human prospect, where risk is quantified, measured and managed to mitigate the perils of the unexpected, and where risk-taking, -transfer and -pooling have become per se sources of legitimate profit. Commenting on Bernstein's work while moving from the Western 'risk' to the Arabic رزق 'rizq', '(God's) sustenance', this paper dares looking at human hazard, زهر 'zahr', the 'dice' of future chances, through a comparative and inter-cultural perspective. More precisely, it aims to show how specific anthropological assumptions result in an alternative theory and practice of risk management in a market whose peculiarity is to operate not 'against' but 'in the Name of God': the market of Islamic finance. To this end, Islamic finance is depicted within an anthropology of time where not only the future, but also the present are a divine (rather than human) creation, and where, consequently, risk is deeply re-framed both as a concept and as a source of legitimate profit. In fact, to the extent to which the future remains an economic opportunity in Islam (Q. II:275: 'Allah has permitted trade'), it is not conceived as a human product but as a part of man's responsibility to perform Shari'ah, as God's agent in the 'real'/'right' (haqq). Thus, while any legitimate profit follows liability (al-kharaj bi-l-daman), risk management coherently endorses the primacy of the real economy, exchange equilibrium (with any unlawful increase from riba, gharar or maysir being prohibited), and profit-loss sharing. In other terms, if risk continues to hold an economic value in Islamic finance, this value exists only as legitimate profit (kharaj) through liability (daman), and remains linked to asset-based and commercial activities. As a result, the logic underpinning Islamic banking and insurance (takaful), as well as securities (sukuk) trade, becomes hardly comparable to the conventional one, and rejects financial products, such as derivatives, that are deemed lacking in any commercial value since nothing 'real' is actually traded. To conclude, the paper remarks on how this alternative history of risk in Islam requires further consideration in financial theory and regulation, for the benefit of a level playing field where both conventional and Islamic finance are able to co-exist and prosper under the same (God's) sky.
Keywords: A12; N20; N25; P48; Z12; 330; islamic finance; risk management; anthropology of risk; comparative economic history